Addressing mental health and wellbeing in a consultation. (5th April 2022) - Fox, Charles; Kilvert, Anne
Abstract: People with diabetes manage their condition 24 hours a day, seven days a week and only about 2% of decisions are made in consultation with a health care professional. Many factors impact on a person's ability to manage their diabetes, and consequently on their mental health and wellbeing. These include everyday life pressures: work, celebrations, holidays and major life events, such as loss of a loved one or a job. Diabetes‐specific stresses include diabetes distress and burnout, fear of hypos and complications, eating disorders and denial, with an increased risk of anxiety and depression. Some people have pre‐existing mental health conditions which lead directly to development of diabetes and add to the challenge of glycaemic management. The health care professional has an important role in supporting people with diabetes with education and technology, but it is crucial that they also address mental health and wellbeing as this impacts on the person's diabetes. In this article, based on a presentation at the Diabetes Professional Care Conference, we contrast the medical and biopsychosocial models of care and discuss the importance of the principles of person‐centred care and empowerment in addressing mental health of people with diabetes. Being empathic and giving the person the opportunity to talk about their feelings is central to this approach. Copyright © 2022 John Wiley & Sons.